Belief and bounded rationality - Jago, Mark (2006)
Predictive accounts of belief ascription, either following the principle of charity or Dennett's intentional stance, have proved popular recently. However, such accounts require us first to treat agents as perfectly rational agents and then revise this assumption as appropriate. I argue that such downwards revision is no easy task and that several proposed accounts are not satisfactory. I propose a way of characterising agent's belief states which shares Dennett's approach but avoids treating agents as perfectly rational, and develop a formal account in terms of fan models.